Towards a unifying approach of the 'new economic geography' - Michael Pflüger; Jens Südekum (Institute for the Study of Labor (IZA), 2006)
Models of the new economic geography share a number of common conclusions, but also exhibit notable differences, in particular with respect to the shape of the location pattern and the efficiency of the market equilibrium. This reflects the fact that these models rely heavily on specific functional forms. In this paper we approach the properties of the 'footloose entrepreneur' class of new economic geography models with a unifying framework based on the indirect utility function of mobile agents. This approach has several payoffs. We are able to provide general, yet handy, formulae to determine the break point, the bifurcation pattern and the welfare properties of the market equilibrium. Moreover, an application of this framework allows us to show how specific results in the literature can be reconciled as special cases, thereby allowing us to highlight the origin of their differences.
Keywords: R12; R50; F12; F15; F22; 330; new economic geography; agglomeration; location pattern; regional policy